Wachstumsabläufe in einer orientalischen Stadt, am Beispiel von Kabul/Afghanistan - Hahn, Helmut (ERDKUNDE, 1972)
The population of Kabul has, during the last 50 years, grown more than five-fold. The structural changes which have occurred as a result of this rapid growth have been studied with the help of mapping and questionnaire exercises carried out in 1968, to reveal not only the main features but also individual phenomena. The main determinant of individual differences is the topographically determined division of the city into two, which hampers a concentration of location factors, but the city's location in the transition area between oriental-islamic and Indian cultures has also been an influence. As is the case all over the Orient, the bazaar in the old town is losing prestige and a modern shopping and government quarter is developing in the neighbouring oldest part of the new town. It appears, however, that a second shopping centre is coming into being in the isolated western newer parts of the town. The combination of shopping and residential functions and its bazaar street character indicate eastern influence. Proper slum formation cannot yet be observed in Kabul, even though the traditional social division of the old city by religion, language, etc. is caught up in complete breakup and a levelling down to a lower social grouping can be observed. The social differentiation of the new area of town follows only income differences. The stream of immigrants - above all of unskilled labourers etc. - pours into the old city, while the new town districts are inhabited primarily by middle and upper class people born in Kabul. In general, immigrants usually only resettle in the newer residential areas after a longer period of residence in the old city and after social and economic integration. Socially weaker strata, in financial grounds, can only afford the rents demanded, or become home owners in the areas of 'wild' building or in the villages of the urbanising area.